CIRI GETARAN MEKANIK DAN ARUS CATU PADA MOTOR LISTRIK INDUKSI 3-FASA AKIBAT EKSENTRISITAS CELAH UDARA - Nurhadi, Indra; Mahyuddin, Andi Isra; Ahmarudin, M (Mesin, 2001)
This paper discusses theoretical and experimental study to determine the signature of stator supply current and stator vibration of 3-phase induction motor resulting from airgap eccentricity. Based on the theoretical study it can be formulated that the signature due to eccentricity is affected by number of slots on the rotor and the stator as well as slip, defined as âPrincipal Slot Harmonics (PSH)â and âDynamics Eccentricity Components (DEC)â. To study its feasibility for practical use a set of experiments was performed and the predicted signature was identified. Using the test rig, it was demonstrated that the magnitude of PSH and DEC in stator current and body vibration increase due to eccentricity.